Determinants Of Effective School Governance: Participation, Reflection, Trust And Leadership Competencies (The Review of Diabetic Studies, 2025)
The effectiveness of school governance is determined not only by formal administrative structures but also by the quality of interaction within pedagogical teams. This study examines four core indicators – the Participation Index, the Collective Reflection and Readiness for Change Indicator, the Trust Coefficient, and the Leadership Competency Rating – as determinants of effective school management. While each of these constructs has been discussed separately in educational and organizational research, their operationalization as an integrated evaluative mechanism for pedagogical teams is introduced here as a novel contribution. Drawing on data collected from secondary schools, the research applies quantitative methods, including correlation and regression analysis, to explore the relationships among participation, trust, reflection, and leadership competencies. The results show that participation and trust exert the strongest direct influence on governance outcomes, whereas reflection and leadership competencies act as supporting factors that reinforce team cohesion and professional development. The findings highlight that effective governance requires a balanced mechanism combining organizational processes with socio-psychological dimensions of teamwork. The proposed framework advances theoretical perspectives on school governance and offers practical guidance for enhancing participatory leadership, fostering trust-based communication, and promoting collaborative innovation in education.